A global review of the invasive aquatic weed Cabomba caroliniana [A. Gray] (Carolina fanwort): Current and future management challenges, and research gaps. (10th December 2021) - Roberts, Jason; Florentine, Singarayer
Abstract: Cabomba caroliniana [A. Gray] (Cabombaceae), also known as Carolina fanwort, is a native of South America which has now become a serious invasive threat to aquatic systems across the world. Its capacity to inundate a water column with active fragments and seeds makes the containment and management of C. caroliniana a challenging task and an ecological and economic necessity. Previous and current management efforts have been largely focussed on biological control, drawdown methods, herbicide application, manual removal, shading and the use of a concentrated urea solution. Although these methods have shown some success in reducing large infestations, they are generally considered to be unreliable when used alone since they are unable to contain or reduce the species in the long term with a single‐use treatment protocol. It is feared that, without effective, improved and integrated management strategies, C. caroliniana will continue to invade aquatic ecosystems beyond its already wide current distribution, thus causing increased global economic and environmental damage. This review will therefore explore the biology and distribution of C. caroliniana and examine the current and previous attempts for its global management. It will also evaluate the most successful current treatments and clarify where research efforts are urgently needed for the improved long‐term extirpation of this aquatic invader.